Transport priorities shaping the urban fabric: new methods and tools - Newman, Peter (2017)
Sustainability for cities can be understood as the process of reducing the footprint of urban development whilst improving liveability (Newman & Kenworthy, 1999). Figure 1.1 schematically describes the city as a process of inputs, dynamics and outcomes, both positive and negative. The city’s footprint can be lowered by reducing the resource inputs and waste outputs while increasing the liveability through better housing, community, health and economic benefits. Transport – a major part of settlements – is the key to understanding and managing city dynamics. This chapter examines how transport infrastructure shapes cities. It also shows how sustainability can be improved by better planning and assessment of transport infrastructure. The chapter uses the newly developed theory of urban fabrics (Newman & Kenworthy, 2015; Newman et al., 2016) as the basis of creating a set of methods for sustainable transport planning and assessment (Newman et al., 2009; Newman, 2013).